Selective Synthesis of Benzaldehydes by Hypochlorite Oxidation of Benzyl Alcohols under Phase Transfer Catalysis - K. Bijudas; P. Bashpa; V. P. Bibin; Lakshmi Nair; A. P. Priya; M. Aswathy; C. Krishnendu; P. Lisha (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The selective synthesis of benazaldehyde and substituted benzaldehydes from corresponding benzyl al-cohols has been carried out by using hypochlorite as an oxidant in organic medium under phase trans-fer catalysis. The reaction is highly selective since no traces of benzoic acid or substituted benzoic acids have been detected and the yield is found to be more than 90%. The products obtained were precipi-tated as 2,4-dinitrophenylhydrazone and the recrystallised products were characterized by melting point and by spectrophotometric techniques like infra red and UV-Visible analysis. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)